Ensino de Geografia. Fronteiras e Horizontes.Porto Alegre, RGS: Editora Compasso, 2012. Autora: Adriana Maria Andreis - Lozano Mesías, Paulina; Salgado Labra, Verónica (Anekumene, 2012)
Ensino de Geografia. Fronteiras e Horizontes.Porto Alegre, RGS: Editora Compasso, 2012. Autora: Adriana Maria Andreis